MODERNIZATION, OPTIMIZATION PROCESS OF REGULATION OF THE LEGAL FRAMEWORK AS A BASIS FOR THE DEVELOPMENT OF THE FINANCIAL SUSTAINABILITY OF MUNICIPALITIES - Elena B. Krylova; Marija V. Beljaeva (Модернизация, инновация, развитие, 2015)
The article highlights the problems associated with the maintenance of financial stability of municipalities. The process of improving the regulatory framework in the public sector of the economy, ensuring the development of economic entities of financial relations at the municipal level, and contributing to the achievement of financial sustainability of municipalities. We consider a number of theses that constitute the theoretical basis of the financial sustainability of municipalities.